A triangular fuzzy demand stochastic process model for IoT. (December 2018) - Fang, Shao
Abstract: In terms of randomness and fuzziness of the inventory control and decision-making process that affect the two-echelon supply chain of textile, this paper proposes to construct a triangular fuzzy demand stochastic process model of textile two-echelon supply chain combined costs. To begin with, the researcher will study the textile two-echelon supply chain to produce the optimal model of combined costs. And then, this paper will try to prove the efficiency of the model.